DEVELOPMENT OF SUSTAINED-RELEASE VILDAGLIPTIN NANOPARTICLES FOR ENHANCED TYPE 2 DIABETES MELLITUS THERAPY - SWAPNIL BHANUDAS GADEKAR; ASHOK VITHAL BHOSALE (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objectives: This study aimed to develop sustained-release vildagliptin (VLG) nanoparticles using ionotropic gelation to enhance therapy for type 2 diabetes mellitus (T2DM). The goal was to optimize formulation parameters to improve drug delivery, prolong therapeutic action, and reduce dosing frequency for better glycemic control. Methods: The nanoparticles were optimized using a Box-Behnken design, focusing on key variables chitosan and dextran sulfate concentrations, along with Tween 80 content. The impact of these factors was assessed on encapsulation efficiency (EE), drug release (DR), and particle characteristics. Further characterization included Fourier-transform infrared (FTIR) and X-ray diffraction (XRD) analyses to confirm drug-polymer compatibility and crystallinity changes. Comparative release studies were conducted between free VLG and nanoparticle formulation, while statistical evaluation was performed using a central composite design. Results: The optimized nanoparticles exhibited a spherical morphology with an average size of 268.18±7.5 nm and a narrow size distribution (polydispersity index=0.427±0.21). FTIR confirmed drug-polymer compatibility, while XRD revealed a shift in VLG from a crystalline to an amorphous state upon encapsulation. The EE ranged from 58.25±1.2% to 84.01±1.8%, demonstrating effective drug loading. DR studies showed that free VLG was completely released within 1 h, whereas the nanoparticle formulation extended release over 24 h, confirming sustained delivery. Conclusion: The findings suggest that the developed VLG nanoparticles can prolong therapeutic action, potentially reducing dosing frequency and improving glycemic control in T2DM. This study highlights the potential of nanotechnology-based delivery systems to enhance the pharmacokinetic profile of antidiabetic drugs, offering a promising strategy for long-term diabetes management.